La promenade au bord de la mer. Variations sur un topos littéraire au tournant des XIXe et XXe siècles en Europe - Florence Godeau (Carnets)
At the turn of the Century, in Europe, many novels or short stories evoke walks along the sea, on the dikes recently upgraded under the growing vogue of stays resorts, or on strike, who conducts to more solitary reveries. We will consider the many variations of this Topical of the promenade along the sea or on the beach, and compare its forms and functions within the various narratives studied.